2015
DOI: 10.1364/josaa.32.001764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of induced transverse chromatic aberration on peripheral vision

Abstract: Transverse chromatic aberration (TCA) is one of the largest optical errors affecting the peripheral image quality in the human eye. However, the effect of chromatic aberrations on our peripheral vision is largely unknown. This study investigates the effect of prism-induced horizontal TCA on vision, in the central as well as in the 20° nasal visual field, for four subjects. Additionally, the magnitude of induced TCA (in minutes of arc) was measured subjectively in the fovea with a Vernier alignment method. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…Even though the resolution acuity at that location is sampling limited with around 3-5 arcmin (Thibos, 1987; Wertheim, 1894), low contrast resolution as well as detection can be limited by the contrast reduction. Such a decrease in peripheral detection acuity due to TCA has indeed been observed in previous studies (Cheney, Thibos, & Bradley, 2015; Venkataraman, Winter, Rosén, & Lundström, 2016; Winter et al, 2015). …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Even though the resolution acuity at that location is sampling limited with around 3-5 arcmin (Thibos, 1987; Wertheim, 1894), low contrast resolution as well as detection can be limited by the contrast reduction. Such a decrease in peripheral detection acuity due to TCA has indeed been observed in previous studies (Cheney, Thibos, & Bradley, 2015; Venkataraman, Winter, Rosén, & Lundström, 2016; Winter et al, 2015). …”
Section: Discussionsupporting
confidence: 83%
“…In the first study, Ogboso and Bedell used a subjective alignment method and found the TCA to increase with eccentricity (Ogboso & Bedell, 1987). In the second study, Winter et al (2015) evaluated the effect of prism-induced TCA on foveal and peripheral vision and found that different prisms were needed to optimize peripheral vision compared with central vision. The reason for the low number of studies on peripheral TCA is due to the difficulties in estimating its magnitude by adequate measurement procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Foveal TCA for example, has been reported to range between approximately 1 arcmin [3,4,7] and up to 3 arcmin [8]. There are only two reports where subjective tests have been used to estimate TCA outside of the fovea [8,9]. The change of TCA as a function of the light bundle’s lateral position in the entrance pupil is governed by a linear relationship (see Figure 4 in [3]).…”
mentioning
confidence: 99%
“…Jaeken et al (2011) yRynders et al (1998), mientras que la aberración cromática transversal sí varía, de acuerdo con) y Winter et al (2015. Sin embargo, sostienen que la aberración cromática transversal apenas influye en tareas visuales en visión excéntrica.…”
unclassified